Biopesticides as a promising alternative to synthetic pesticides: A case for microbial pesticides, phytopesticides, and nanobiopesticides - Ayilara, Modupe S.; Adeleke, Bartholomew S.; Akinola, Saheed A.; Fayose, Chris A.; Adeyemi, Uswat T.; Gbadegesin, Lanre A.; Omole, Richard K.; Johnson, Remilekun M.; Uthman, Qudus O.; Babalola, Olubukola O. (Frontiers in microbiology, 2023)
Over the years, synthetic pesticides like herbicides, algicides, miticides, bactericides, fumigants, termiticides, repellents, insecticides, molluscicides, nematicides, and pheromones have been used to improve crop yield. When pesticides are used, the over-application and excess discharge into water bodies during rainfall often lead to death of fish and other aquatic life. Even when the fishes still live, their consumption by humans may lead to the biomagnification of chemicals in the body system and can cause deadly diseases, such as cancer, kidney diseases, diabetes, liver dysfunction, eczema, neurological destruction, cardiovascular diseases, and so on. Equally, synthetic pesticides harm the soil texture, soil microbes, animals, and plants. The dangers associated with the use of synthetic pesticides have necessitated the need for alternative use of organic pesticides (biopesticides), which are cheaper, environment friendly, and sustainable. Biopesticides can be sourced from microbes (e.g., metabolites), plants (e.g., from their exudates, essential oil, and extracts from bark, root, and leaves), and nanoparticles of biological origin (e.g., silver and gold nanoparticles). Unlike synthetic pesticides, microbial pesticides are specific in action, can be easily sourced without the need for expensive chemicals, and are environmentally sustainable without residual effects. Phytopesticides have myriad of phytochemical compounds that make them exhibit various mechanisms of action, likewise, they are not associated with the release of greenhouse gases and are of lesser risks to human health compared to the available synthetic pesticides. Nanobiopesticides have higher pesticidal activity, targeted or controlled release with top-notch biocompatibility and biodegradability. In this review, we examined the different types of pesticides, the merits, and demerits of synthetic pesticides and biopesticides, but more importantly, we x-rayed appropriate and sustainable approaches to improve the acceptability and commercial usage of microbial pesticides, phytopesticides, and nanobiopesticides for plant nutrition, crop protection/yield, animal/human health promotion, and their possible incorporation into the integrated pest management system.